High‐latitude GPS phase scintillation from E region electron density gradients during the 20–21 December 2015 geomagnetic storm. Issue 7 (3rd July 2017) - Loucks, Diana; Palo, Scott; Pilinski, Marcin; Crowley, Geoff; Azeem, Irfan; Hampton, Don
Abstract: A novel operating mode for Poker Flat Incoherent Scatter Radar (PFISR) has been developed to support the study of GPS L1 scintillations arising from electron density gradients over Alaska. Previous authors have combined GPS scintillation data with either PFISR or multispectral imagery in this region. This analysis combines all three techniques to determine both gradient parameters as well as the most likely ionospheric source, including a conjunction analysis between GPS signals and known PFISR beams. This approach was used to study scintillation events observed in December 2015. These events were recorded during the recovery phase of a geomagnetic storm that ensued on 20 December when the Earth passed through the path of a solar CME (DST minimum near −170 nT, K p peak of 7). Two scintillation events were detected through analysis of the phase scintillation index ( σ ϕ ), calculated from an Atmospheric and Space Technology Research Associates' Connected Autonomous Space Environment Sensor GPS receiver at Poker Flat. Values of σ ϕ ≃0.5 and σ ϕ ≃1.6 cycles were recorded for these events. Concurrently, an experiment on PFISR was run to discern the electron density along the GPS signal line of site, and the imager observed the 428.7 nm, 557.7 nm, and 630.0 nm emission lines during the experiment window. From the ratios of derived emission intensities, estimates of precipitating particle energies were made allowing confirmation of the altitudes associated with the electron density peaks determined using raw radar returns from PFISR. Results indicate that temporal and spatial electron density gradients existed along the signal's path during periods of highest scintillation, which resulted from impact ionization from auroral particle precipitation at E region altitudes. Plain Language Summary: A novel radar operating mode has been developed to support the study of GPS L1 scintillations arising from ionospheric phenomena occurring over Alaska between 100 km and 400 km altitudes. This is the first in a radar experiment campaign to determine which of higher‐ or lower‐altitude phenomena have the most impact on GPS signals in Alaska. This analysis combines multiple observation techniques to determine source phenomena and their parameters. This approach was used to study scintillation events observed on 20 and 21 December 2015 that occurred in conjunction with a moderate geomagnetic storm. A high‐resolution GPS receiver was employed with a radar experiment run to discern ionospheric parameters along the path of the GPS signal, and an all‐sky imager observed the red, green, and blue emission lines during the experiment window. From the ratios of derived emission intensities, estimates of precipitating particle energies were made allowing confirmation of the altitude ranges associated with radar‐derived ionospheric phenomena. Results indicate that a dynamic ionosphere existed along the signal's path during periods of highest scintillation, which resulted from auroral particle precipitation down to around 130 km altitude. Key Points: GPS phase scintillation detected at Poker Flat during 20–21 December 2015 geomagnetic storm PFISR detected E region electron density gradients along the GPS ray path All‐sky imagery detected dynamic auroral arcs consistent with the scintillation and gradients